Melatonin protects against oxidative organ injury in a rat model of sepsis - YEGEN, BERRAK; ERCAN, FERİHA; ŞENER, GÖKSEL (SPRINGER, 2005)
Purpose. Based on the potent antioxidant effects of melatonin, we investigated the putative protective role of melatonin against sepsis-induced oxidative organ damage in rats. Methods. Sepsis was induced by cecal ligation and puncture (CLP) in Wistar albino rats. Animals subjected to CLP and sham-operated control rats were given saline or melatonin 10 mg/kg intraperitoneally 30 min before and 6 h after the operation. The rats were killed 16 h after the operation and the biochemical changes were investigated in the liver, kidney, heart, lung, diaphragm, and brain tissues by examining malondialdehyde (MDA) and glutathione (GSH) levels, and myeloperoxidase (MPO) activity. We also examined the tissues microscopically. Results. Sepsis resulted in a significant decrease in GSH levels and a significant increase in MDA levels and MPO activity (P < 0.05-P < 0.001) showing oxidative damage, which was confirmed by histological examination. Melatonin clearly reversed these oxidant responses and the microscopic damage, demonstrating its protective effects against sepsis-induced oxidative organ injury. Conclusion. The increase in MDA levels and MPO activity and the concomitant decrease in GSH levels demonstrate the role of oxidative mechanisms in sepsis-induced tissue damage. Melatonin, by its free radical scavenging and antioxidant properties, ameliorated oxidative organ injury. Thus, supplementing antiseptic shock treatment with melatonin may be beneficial in the clinical setting.
Keywords: sepsis; melatonin; lipid peroxidation; glutathione; myeloperoxidase activity; ISCHEMIA-REPERFUSION; FREE-RADICALS; NITRIC-OXIDE; INFLAMMATION; GLUTATHIONE; DAMAGE; MYELOPEROXIDASE; ENDOTHELIUM; PERITONITIS; DYSFUNCTION